Determinants of Bank Competition in Morocco and Evaluation of Structural Reforms - Hakam, Afifa; Fatine, Filali Adib; Zakaria, Firano (International Journal of Economics and Financial Issues, 2013)
The empirical results of this paper indicate that the degree of competition in the banking system is determined by several macroeconomic aggregates that describe the relevance of the policies implemented in financial Morocco. Thus, the result shows that there is a positive relationship between the index of competition and concentration there by verifies our theoretical perception. On another note, economic growth is negatively correlated with the competition, which unfortunately indicates that when there are sustained economic growth banks does not behave concurrently and try to retain their market share stimulated by a high concentration sector. This is also dependent on conditions in the credit market, which indicates that when the demand is constant, banks tend to have fewer competing behaviors. In addition, the development of positive market impact of competition which is consistent with liberal theory. Thus, the use of financial market intensifies competition between banks to produce services being able to attract more customers to compensate for those who chose the stock market. Finally, in the implementation of monetary policy, the indicator of interbank interest rate has a positive impact on competition. Keywords: Competition; Concentration; Financial Stability; Public policy; Economic Growth JEL Classifications: D41; G21